THE EFFECT OF INNOVATION ON F&B MMSMEs IN MALANG CITY - Dian Candra Dewi; Sudarmiatin Sudarmiatin; Agus Hermawan (Journal of Management and Informatics, 2022)
The purpose of this study was to examine the effect of marketing innovation, product innovation, and cafe atmosphere on purchasing decisions in F&B MSMEs. The sampling technique used was purposive sampling. The research uses qualitative methods with a descriptive approach and quantitative methods in data processing for hypothesis testing. Hypothesis testing uses a structural regression approach with Smart-PLS 3.0 software using the t-test at a significance level of 5%. The choice of software is because this study uses path analysis with a sample size of 75 F&B MSMEs consumers in Malang City